Aspects of 6th generation sensing technology: from sensing to sense - Mazumdar, Hirak; Khondakar, Kamil Reza; Das, Suparna; Kaushik, Ajeet (Frontiers in Nanotechnology, 2024)
The 6th-generation (6G) sensing technology is transforming the ways we perceive and interact with the world in real scenarios. It combines advanced materials, sophisticated algorithms, and connectivity to create intelligent, context-aware systems that can interpret and respond to environmental stimuli with unprecedented accuracy and speed. The key advancements include 1) ultra-sensitive sensors capable of detecting physical, chemical, and biological changes at low concentrations, 2) the integration of artificial intelligence (AI) and machine learning (ML) for enhanced data processing, and 3) the deployment of IoT networks with 5th-generation (5G) for seamless data transmission and real-time analysis. These cutting-edge technologies create immersive environments where devices capture data and anticipate user needs and environmental conditions. The 6G sensing technology has potential applications across sectors like point-of-care (PoC), healthcare, urban planning, and environmental monitoring. The transition from sensing to sense-making represents a paradigm shift, fostering a more intuitive, responsive, and interconnected world. The article provides a comprehensive overview of the current state and prospects of 6G sensing technology, highlighting its transformative potential and the challenges in realizing its full capabilities